Recognition and Redistribution Policies in Undergraduate Retention - Maíra Tavares Mendes (Universidade Federal do Rio Grande do Sul, 2021)
The objective of the text is to analyze the articulation of inequalities arising from the entry of new subjects into university, such as class, race, gender, sexuality and disability. To this end, the text is divided into three parts: 1) conception of student retention as one of the dimensions of access, and therefore an affirmative policy arising from access policies; 2) discussion of the correlated concepts of markers of difference and categories in articulation, and their usefulness in thinking about student retention; 3) the advocating of the need to coordinate redistribution and recognition policies (as of Nancy Fraser's contribution) on student retention.